“Emotion Detection from Brain and Audio Signal - Wandile, Priyanka A.; Mr.Pratik Hajare, Dr.Narendra Bawane2 , (International Journal of Scientific Research and Management (IJSRM), 2015)
In this paper reports on the human emotion recon- ignition using different set of electroencephalogram (EEG) channels using discrete wavelet transform. Emotion recognition could be done from the text, speech, and facial. We concentrate on recognition of “inner” emotions from electroencephalogram (EEG) signals as humans could control their facial expressions or vocal intonation. In this system work EEG signals have been used to extract the feature, the feature is extracted by using wavelet transform such as Db6. After extracting the feature signal is given to Neural Network for classification. In the past few days, many studies have been done on emotion recognition. Anderson utilized facial expressions to recognize emotion. However, these signals shared the same disadvantage. They are not reliable or perfection is not there to detect emotion, especially when people want to conceal their feelings. In this paper, The EEG-based emotion recognition algorithm based on spectral features and neural network classifiers is proposed